How Firms Can Strategically Influence Open Source Communities c y Viktor Lee. - Lee, Viktor; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Firms have discovered that open source (OS) communities can be valuable sources of innovation. However, the access for firms to these communities turned to be intricate. One proven way of how firms can enter OS communities is via their personnel ((3z(Bmen on the inside(3y(B). Focusing on firm-sponsored OS communities, Viktor Lee detects the specific functions of MOI and how these individuals influence the community network by applying a comparative case study of two OSS firms. A netnographic and social network analysis of the community interactions of over 12,000 individuals was conducted. He concludes that firms can succeed in integrating a community into the firm$1 (Bs development process with the help of the MOI.s
Keywords: Economics; Economics/Management Science; Innovation/Technology Management